Indigenous People of Biafra in the Frames of Two Nigerian Dailies - Shehu, Abubakar; Bello, Faruk Nanoh (NIU Journal of Humanities, 2019)
The study centred on the newspapers’ framing of Indigenous people of Biafra in their struggle for independence among the two widely read media outlets of Nigeria involving Daily Trust and The Nation newspapers. The study was anchored on framing theory that explains how media shape audience thinking. Content analysis was the chosen method. The study adopted a purposive sampling technique for the newspapers and the periods under study and a random sampling for the editions. A coding sheet was designed as the instrument. The data gathered were then subjected to SPSS analysis using figures. The study found that Indigenous people of Biafra were blamed by the frames on many fronts; that there were a lot of negative frames in the media reportage against them. The study therefore recommended that the government dialogue with this Igbo group on issues of alleged marginalization and unfair treatment meted out to them, that the media should be unbiased in reporting the group and their ordeals. Keywords: Frames, Nigeria, Indigenous people of Biafra, Dailies.